A Little - Known Story About A Movement , A Magazine , And The Computer 's Arrival In Art : New Tendencies And Bit International , 1961 - 1973 - Rosen, Margit (Cambridge ZKM/Center for Art and Media, 2011)
When Zagreb was the epicenter of explorations into the aesthetic potential of the new “thinking machines.”This book documents a short but intense artistic experiment that took place in Yugoslavia fifty years ago but has been influential far beyond that time and place: the “little-known story” of the advent of computers in art. It was through the activities of the New Tendencies movement, begun in Zagreb in 1961, and its supporting institution the Galerija suvremene umjetnosti that the “thinking machine” was adopted as an artistic tool and medium. Pursuing the idea of “art as visual research,” the New Tendencies movement proceeded along a path that led from Concrete and Constructivist art, Op art, and Kinetic art to computer-generated graphics, film, and sculpture. With their exhibitions and conferences and the 1968 launch of the multilingual, groundbreaking magazine Bit International, the New Tendencies transformed Zagreb?already one of the most vibrant artistic centers in Yugoslavia?into an international meeting place where artists, engineers, and scientists from both sides of the Iron Curtain gathered around the then-new technology. For a brief moment in time, Zagreb was the epicenter of explorations of the aesthetic, scientific, and political potential of the computer. This volume documents that exhilarating period. It includes new essays by Jerko Denegri, Darko Fritz, Margit Rosen, and Peter Weibel; many texts that were first published in New Tendencies exhibition catalogs and Bit International magazine; and historic documents. More than 650 black-and-white and color illustrations testify to the astonishing diversity of the exhibited artworks and introduce the movement's protagonists. Many of the historic photographs, translations, and documents are published here for the first time. Taken together, the images and texts offer the long overdue history of the New Tendencies experiment and its impact on the art of the twentieth century
- 1961 Nove tendencije Preparation Almir Mavignier Letter to Matko Mestrovic Bozo Bek Letter to Mary Bauermeister Almir Mavignier Letter to Matko Mestrovic Nove tendencije Exhibition Matko Mestrovic Radosla Artists' Commentaries - 1962-1963 L'Instabilite Francois Morellet The Case for Programmed Experimental Painting Groupe de Recherche d'Art Visuel Nouvelle Tendance Arte programmata. arte cinetica, opere moltiplicate, opera aperta Umberto Eco Arte Programmata Meeting of the Nouvelle Tendance Oltre la pittura. Oltre la scultura. Mostra di ricerche di arte visiva - 1963-1964 nove tendencije 2 Matko Mestrovic Artists' Commentaries Timeline Francois Molnar and Francois Morellet For a Progressive Abstract Art Nouvelle Tendance - recherche continuelle Bulletin No. 1 nuova tendenza 2 neue tendenzen - 1964-1965 Propositions visuelles du mouvement international Nouvelle Tendance Karl Gerstner What Is the Nouvelle Tendance? Arte Programmata. Kinetic Art Bruno Munari Arte Programmata - 1965 nova tendencija 3 Editorial Board Remarks Giulio Carlo Argan Aas Research Waldemar Cordeiro Semantic Concrete Art Dimitrije Basicevic Actuality of Functional Art Anonima Group Abraham A. Moles Cybernetics and the Work of Art Matko Mestrovic and Radoslav Putar Brezovica, August 18, 1965 Working Meeting of the Participants of NT3 Francis Hewitt Zagreb from Michelangelo 1968 tendencife 4 / tendencies 4 Preparation Radoslav Putar, Dimitrije Basicevic, Boris Kelemen, Ivan Picelj and Bozo Bek nt4 program for 1968 Radoslav Putar, Dimitrije Basicevic, Boris Kelemen, Ivan Picelj, Vjenceslav Richter and Bozo Bek Continuation of the Discussion about the Concept of nt4 on December 6, 1967 Program Information 1 tendencija 4 Program Information 7 tendencije 4 / tendencies 4 Waldemar Cordeiro Letter to Bozo Bek Information exhibition accompanying the colloquy tendencije 4. "Kompjuteri i vizuelna istrazivanja" tendencies 4. "Computers and Visual Research" tendencije 4"Kompjuteri i vizuelna istrazivanja" tendencies 4. "Computers and Visual Research" Abraham A. Moles Introduction to the Colloquy Vjenceslav Richter Dilemma Alberto Biasi Situation 1967 Frieder Nake Reply to Alberto Biasi Vladimir Bonacic Capabilities of the Computer in Visual Research Branimir Makanec The Role of Interaction in Artistic Expression by Means of Computer Marc Adrian Jiri Valoch Computer. Creator or Tool? Meeting of the t-4 Organizational Board Program Information 10 tendencije 4 / tendencies 4 Program Information 11 tendencije 4 / tendencies 4 \ bit international 1teorija informacija i nova estetika bit international 1. the theory of information and the new aesthetics Why bit Appears Max Bense Aesthetics and Programming Abraham A. Moles Experimental Aesthetics in the New Consumer Society bit international 2kompjuteri i vizuelna istrazivanja bit international 2computers and visual research Magazine Jerko Denegri A New Perspective: Computers and Visual Research Hiroshi Kawano The Aesthetics for Computer Art A. Michael Noll The Digital Computer as a Creative Medium Georg Nees Computer Graphics and Visual Complexity bit international 3. internacionalni kolokvij kompjuteri i vizuelna istrazivanja, zagreb, 3-4 kolovoz 1968 bit international 3. international colloquy computers and visual research, zagreb, august 3-4 1968 Magazine - 1969 tendencije 4. nove tendencije 4 tendencies 4. new tendencies 4 Anonymous tendencije 4 / tendencies 4 Radoslav Putar New Tendencies 4 Almir Mavignier nove tendencije 1 -- A Surprising Coincidence tendencije 4. kompjuteri i vizuelna istrazivanja tendencies 4. computers and visual research Boris Kelemen Computers and Visual Research Program Information 13 tendencije 4 / tendencies 4 Vladimir Bonacic Art as a Function of Subject, Cognition, and Time Compos 68 (J. B. Bedaux, J. Clausman, A. Veen) "Definitions..." Marc Adrian, Gottfried Schlemmer, and Horst Wegscheider SYSPOT tendencije 4typoezija / tendencies 4. typoezija tendencije 4. "Kompjuteri i vizuelna istrazivanja" tendencies 4. "Computers and Visual Research" Symposium Vera Horvat-Pintaric Today's Research and Tomorrow's Society Martin Krampen Psychological Aspects of Man-Computer Relations Untitled Karl Gerstner Producing Art with the Computer G. Hyde, J Benthall, and G. Metzger Zagreb Manifesto Gustav Metzger Leonardo e Laura Mosso Computers and Human Research: Programming and Self-Management of Form Kurd Alsleben The Philosophy of Visual Research Herbert W. Franke Social Aspects of Computer Art Josef Hlavacek On the Interpretation of Programmed Art Gary Rice For ARC: Cybernetics Proposal bit international 4. dizajn bit international 4. design Magazine Gui Bonsiepe Science and Design bit international 5/6. oslikovljena rijec. konkretna poezija bit international 5/6. the word image. poesie concrete Zeljko Bujas First Croatian Literary Texts Computer-Processed 1971 "Umjetnost i kompjuteri 71" / "Art and Computers 71" Colloquy Jonathan Benthall The Computer as a Medium Frieder Nake There Shoul